Assessment of MIC Increases with Meropenem-Vaborbactam and Ceftazidime-Avibactam in TANGO II (a Phase 3 Study of the Treatment of CRE Infections). (4th October 2017) - Lomovskaya, Olga; Castanheira, Mariana; Vazquez, Jose; Kaye, Keith S; Nelson, Kirk; Sun, Dongxu; Alexander, Elizabeth; Dudley, Michael N; Yin, Michael
Abstract: Background: TANGO II is a Phase 3 comparative trial of meropenem-vaborbactam (M-V) given as monotherapy vs. best available therapy (BAT) in patients with bacteremia, cUTIs, cIAI, or HABP/VABP due to CRE. Patients in the BAT arm could receive ceftazidime-avibactam (C-A) as monotherapy. Changes in MIC in bacterial isolates to M-V or C-A recovered during monotherapy were assessed. Methods: MICs were conducted on baseline and post-baseline isolates of Enterobacteriaceae (ENT) recovered during treatment. MICs were determined using CLSI reference methods and MIC changes ≥4 were further assessed. Whole genomes of the majority of isolates were sequenced using Illumina MiSeq platform. Transcription level of various genes was determined using RT-PCR. Results: 25 patients treated with M-V and 4 treated with C-A had KPC-producing ENT. The mean days of treatment was 8.5 and 8.4 for M-V and C-A, respectively. One patient treated with M-V who carried KPC-3-producing K. pneumoniae (KP) (1/25; 4.0%) had a subsequent clinical isolate with a ≥4-fold change in M-V MIC (0.25 to 1 µg/mL), but remained susceptible after 6 days of therapy for acute pyelonephritis; the MIC increase was associated with overexpression of AcrAB, and no mutations in bla KPC-3 were observed. Two of the 4 patients treated with C-A (2/4; 50%) had a post-baseline clinical isolate of KP with ≥4-fold increase in MIC compared with the baseline isolate. In one case, the C-A MIC of the KPC-2-producing isolate increased >128-fold (0.5 to >64 µg/mL) following 7 days of therapy for a complicated intra-abdominal infection (cIAI). Resistance was associated with a point mutation in the bla KPC-2 gene leading to D179Y amino acid substitution in the enzyme, downregulation of genes encoding porins OmpK35 and OmpK36, and upregulation of the efflux operon, acrAB . In the second case, the C-A MIC of the KPC-3 producing isolate increased 8-fold (1 µg/mL to 8 µg/mL) after 14 days of therapy for cIAI; this change in MIC was associated with downregulation of ompK36 and acquisition of a plasmid-containing bla CTX-M-15 and bla OXA-1 genes. Conclusion: M-V appears to be associated with a lower incidence of in vitro MIC changes compared with C-A. Based on these findings, M-V may be a viable treatment option for infections due to KPC-producing CRE. Disclosures: O. Lomovskaya, The Medicine's Company: Employee and Shareholder, Salary; M. Castanheira, Wockhardt Bio Ag: Research Contractor, Research grant; K. S. Kaye, Xellia: Consultant, Consulting fee; Merck: Consultant and Grant Investigator, Consulting fee and Research support; The Medicines Company: Consultant and Grant Investigator, Consulting fee and Research support; K. Nelson, The Medicines Company: Employee, Salary; D. Sun, The Medicines Company: Employee, Salary; E. Alexander, The Medicines Company: Shareholder, Salary; M. N. Dudley, The Medicine's Company: Employee and Shareholder, Salary; M. Yin, Gilead Sciences: Consultant, Consulting fee